ANALISIS LAYANAN REPOSITORI UNIVERSITAS DIPONEGORO BERDASARKAN AKSESIBILITAS, TAMPILAN, DAN ISI: UPAYA PEMBERDAYAAN REPOSITORI BERBASIS RISET - Jumino, Jumino; Suwanto, Sri (BACA: Jurnal Dokumentasi dan Informasi, 2019)
This study aims to analyze how the appearance, accessibility, contents, and to empower the IR UNDIP. The research method used is qualitative by using in-depth interviews, observation, documentation, and FGD as a method of data collection. Data processing is done by reducing and verifying data. The results showed that: (1) the display used by IR UNDIP was considered too simple, monotonous, and less user friendly; (2) the contents of the repository, must be complete and varied, according to the study programs available at the university; 3) increasing the ease of access of IR UNDIP needs to be considered, by providing instructions on how to log in by users and to increase the speed of wifi.